Underground structures in Mars excavated by tunneling methods for sheltering humans. (April 2017) - Sheshpari, Morteza; Fujii, Yoshiaki; Tani, Takuya
Abstract: Humans can inhabit other planets in future by advancement in science and technology, starting by closest ones and moving to farther planets. There are some projects underway currently for human settlement on Mars such as Mars-one project or new proposals by NASA. In this paper, possibility of creating and using underground structures in Mars for sheltering humans against harsh environment and dangerous rays goes under investigation. Primary locations such as Arsia Mons for early settlement on Mars was investigated providing its appropriate conditions. Numerical analysis for tunneling to create underground space was conducted considering different spatial orientation of main discontinuities such as fault and joints in Martian gravity. It was inferred that tunneling in near surface Martian rocks is not susceptible to major failures and instabilities. Frozen water in Mars climate, and low gravity result in lower amounts of required cohesion value to keep tunneling structure stable in different scenarios of discontinuities in Martian rocks. It was concluded that underground structures are among the best options for residing humans on Mars and sheltering them against harsh climate by providing insulation and creating enough thickness of burden rock mass against dangerous cosmic and solar rays.